Improving Students’ Writing Ability through Clustering in the Second Year of SMPN 03 Bonai Darussalam - Dewi Yupita Sinaga; Fitri Susanti; Amelia Rinanda (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study was carried out to improve the students’ writing ability through Clustering Technique in the second year of SMPN 03 Bonai Darussalam academic year 2022 - 2023. The subjects of this study were consisted of 31 students. The method used in this study was Classroom Action Research (CAR). The classroom action research design applied in this study was a collaborative classroom action research. It meant that the writer collaborated with the English teacher of MPN 03 Bonai Darussalam as an observer and collaborator. This study was conducted following Kurt Lewin model with the following procedures of the action research: planning, acting, observing, and reflecting. The study was carried out in two cycles. Each cycle consisted of two meetings. The data were gathered in this study through interview, field notes, questionnaire, and test. The result of the study showed that there was improvement of students’ writing ability. Most of the students gradually gained good scores at the end of each cycle. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English lesson was 70 (seventy). The students’ mean score in preliminary study was 55.85. The mean score in the first cycle was 66.13. The mean score in the second cycle was 73.19. In addition, there was a positive response from the English teacher about implementing the action. In conclusion Clustering Technique could improve students’ writing ability. Key words: Students’ Writing Ability, Clustering Technique, Classroom Action Research